IMPLEMENTASI FUZZY TSUKAMOTO UNTUK PENYAKIT HIPOTERMIA MENGGUNAKAN SELIMUT PEMANAS ELEKTRIK - Amelia Wulan Sari Sapitri; Noorhikmah Fitriani (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Hypothermia is a body condition that occurs in humans under certain conditions where a person's body temperature decreases from normal conditions in general. However, this disease can be overcome using a warm blanket or other clothing that can warm the body. But sometimes the use of this blanket is still not optimal to increase the body temperature of someone who is experiencing cold levels than usual or during extreme weather. To overcome the conditions that occur, technology is now increasingly modern where the blankets that we usually use only use ordinary cloth or filled with cotton, but now blankets that use electric technology have been found that can increase the body more than blankets in general.